(untitled) (Herald of Journalism, 2018)
The article deals with the content and meaning of the terms and definitions of oral publicizm, their features and specificities are confirmed by specific examples. These terms have a place in the Kazakh folklore, oral tradition, but they have not been previously used in the scientific circle. By relying on the term formation and word formation, the author defines and justifies the Kazakh version of borrowed European words. After analyzing the reports (okigat) in radio programs, the author proves his main idea.